PENGARUH INFLASI DAN SUKU BUNGA TERHADAP RETURN SAHAM MANUFAKTUR SEKTOR INDUSTRI DI BEI PERIODE 2018-2023 - Lestari, Lia Wulan; Saparuddin M, Saparuddin M (Yayasan Education and Social Center, 2025)
Stocks as an economic instrument are now becoming a favorite among the public, especially attracting high attention from young people or millennials. Factors that can affect stock returns are economic conditions, inflation, interest rates, dividends, company performance and so on. Therefore, inflation and interest rate factors play a key role in influencing stock returns, high inflation can harm company profitability and people's purchasing power. A hypothesis suggests that inflation has a negative effect on stock returns. On the other hand, low interest rates can stimulate investment and economic growth. This research is a quantitative study to develop and use mathematical models, theories, or hypotheses related to other phenomena. This article conducts research on